2023
DOI: 10.3390/ijerph20042912
|View full text |Cite
|
Sign up to set email alerts
|

Superheroes or Super Spreaders? The Impact of the COVID-19 Pandemic on Social Attitudes towards Nurses: A Qualitative Study from Poland

Abstract: The social perception of the nursing profession in Poland is profoundly affected by social stereotypes that may discourage young people from entering the profession and lead to prejudice towards nurses. During the COVID-19 pandemic, nurses gained visibility, which caused the social image of nurses to likewise grow. In this study, we explore nurses’ experiences with respect to how the COVID-19 pandemic influenced the social image of nursing. Semi-structured interviews were conducted with fifteen hospital nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
1
0
1
Order By: Relevance
“…In a study conducted in Malaysia by Saidun and Akhmetova in 2021, it was revealed that people’s perception of nursing image which was previously negative became positive, and that today, the society perceived nursing as a noble profession [ 27 ]. The following statements reported in a qualitative study conducted with Polish nurses by Walowska and Domaradzki in 2023 on their perspectives of nursing after the COVID-19 pandemic were quite noteworthy [ 28 ]:…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Malaysia by Saidun and Akhmetova in 2021, it was revealed that people’s perception of nursing image which was previously negative became positive, and that today, the society perceived nursing as a noble profession [ 27 ]. The following statements reported in a qualitative study conducted with Polish nurses by Walowska and Domaradzki in 2023 on their perspectives of nursing after the COVID-19 pandemic were quite noteworthy [ 28 ]:…”
Section: Discussionmentioning
confidence: 99%
“…En este estudio, los participantes relataron que la pandemia ha ayudado a difundir la imagen de los profesionales como trabajadores altamente calificados e independientes y, a su vez, ayudó a mejorar la autoestima y la identidad profesional de estos. (28) La mención a la primera línea también se asocia a la distinción de la visibilidad/invisibilidad. Un aspecto se observa en las menciones a largas jornadas laborales del personal de salud.…”
Section: Discussionunclassified